Body of Evidence: Do Autopsy Findings Impact Medical Malpractice Claim Outcomes?. Issue 8 (December 2021) - Gartland, Rajshri M.; Myers, Laura C.; Iorgulescu, J. Bryan; Nguyen, Anthony T.; Yu-Moe, C. Winnie; Falcone, Bianca; Mitchell, Richard; Kachalia, Allen; Mort, Elizabeth
Abstract : Objective: Clinicians may hesitate to advocate for autopsies out of concern for increased malpractice risk if the pathological findings at time of death differ from the clinical findings. We aimed to understand the impact of autopsy findings on malpractice claim outcomes. Methods: Closed malpractice claims with loss dates between 1995 and 2015 involving death related to inpatient care at 3 Harvard Medical School hospitals were extracted from a captive malpractice insurer's database. These claims were linked to patients' electronic health records and their autopsy reports. Using the Goldman classification system, 2 physician reviewers blinded to claim outcome determined whether there was major, minor, or no discordance between the final clinical diagnoses and pathologic diagnoses. Claims were compared depending on whether an autopsy was performed and whether there was major versus minor/no clinical-pathologic discordance. Primary outcomes included percentage of claims paid through settlement or plaintiff verdict and the amount of indemnity paid, inflation adjusted. Results: Of 293 malpractice claims related to an inpatient death that could be linked to patients' electronic health records, 89 claims (30%) had an autopsy performed by either the hospital or medical examiner. The most common claim allegation was an issue with clinician diagnosis, which was statistically less common in the autopsy group (18% versus 38%, P = 0.001). There was no difference in percentage of claims paid whether an autopsy was performed or not (42% versus 41%, P = 0.90) and no difference in median indemnity of paid claims after adjusting for number of defendants ($1, 180, 537 versus $906, 518, P = 0.15). Thirty-one percent of claims with hospital autopsies performed demonstrated major discordance between autopsy and clinical findings. Claims with major clinical-pathologic discordance also did not have a statistically significant difference in percentage paid (44% versus 41%, P > 0.99) or amount paid ($895, 954 versus $1, 494, 120, P = 0.10) compared with claims with minor or no discordance. Conclusions: Although multiple factors determine malpractice claim outcome, in this cohort, claims in which an autopsy was performed did not result in more paid outcomes, even when there was major discordance between clinical and pathologic diagnoses. Abstract : Supplemental digital content is available in the text.